The Effectiveness Of Awig-Awig On Merariq Age Maturation In Prevention Of Early Marriage In Kekait Village - Hamdi Hamdi; Fitriani Amalia; Sahrul Sahrul (Faculty of Law, University of Mataram, 2022)
Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning Marriage Article 7 reads,